2021
DOI: 10.3390/ijerph18179267
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Social Components of Recovery Following Anterior Cruciate Ligament Reconstruction in Young Athletes: A Narrative Review

Abstract: Anterior cruciate ligament (ACL) rupture is a common injury in young athletes. To restore knee stability and function, patients often undergo ACL reconstruction (ACLR). Historically, there has been a focus in this population on the epidemiology of ACL injury, the technical aspects of ACL reconstruction, and post-operative functional outcomes. Although increasingly recognized as an important aspect in recovery, there remains limited literature examining the psychological aspects of post-operative rehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…Previous studies have found lower self-esteem and mood disturbances correlated with poorer ACL recovery. 19,20 Our findings demonstrate the impact psychologic distress on postoperative function in a wider surgical cohort. Given that the most common primary CPT code in the study cohort was ACL reconstruction, this suggests that hindered return to sport and recovery seen in those with mental health conditions may be secondary to poorer postoperative function as measured by PROMIS PF and IKDC.…”
Section: Accepted Manuscriptmentioning
confidence: 62%
“…Previous studies have found lower self-esteem and mood disturbances correlated with poorer ACL recovery. 19,20 Our findings demonstrate the impact psychologic distress on postoperative function in a wider surgical cohort. Given that the most common primary CPT code in the study cohort was ACL reconstruction, this suggests that hindered return to sport and recovery seen in those with mental health conditions may be secondary to poorer postoperative function as measured by PROMIS PF and IKDC.…”
Section: Accepted Manuscriptmentioning
confidence: 62%
“…Tripp et al. [ 81 ] used the short version of the POMS scale (S-POMS) to find out that the more negative emotions, the lower confidence of athletes to return to sports, and the greater fear of reinjury [ 56 ].…”
Section: Common Psychological Evaluation Methods After Aclrmentioning
confidence: 99%
“…Vutescu et al. [ 56 ] considered that psychological factors, including self-esteem, were related to the RTS potential of young athletes.…”
Section: Psychological Factors Affecting Rts After Aclrmentioning
confidence: 99%
“…[16] Variation exists in the risk of injury, which suggests the presence of specific quality indicators or rehabilitation milestones that potentially impact RTS outcomes. [16,17] Other than the surgical methods used for ACLR, other important factors influence recovery and RTS in PSPs, including age, [18] gender, [18][19][20] body mass index (BMI), [21] level of physical therapy, [22] rehabilitation protocol, [23] intent to RTS, [24] and psychological readiness. [25] The post-ACLR RTS rate among athletes younger than 25 is higher than older athletes.…”
Section: Introductionmentioning
confidence: 99%